Hukum Islam dan Politik Hukumnya dalam Hukum Nasional - Syaifullahil Maslul (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2019)
AbstractDevelopment of National law must pay attention to many aspects, one of which is Islamic law. Islamic law itself has become part of three main sources of law that build national law, namely Islamic law, customary law and western law. Thus, it is important to understand how the legal basis and politics of Islamic law is in the development of national law in the future. This study was conducted in a normative and sociological approach, that Islamic law is guided and preserved by Muslim communities. The results of this study showed; first, the Islamic legal basis in National law is the first principle of the Pancasila and Article 28 E paragraph (1), (2) and Article 29 of the constitution. Pancasila and a quo Articles are not only guarantee the implementation of ubudiyah, but also which are divided into muamalat, munakahat, and jinayat. Various rules have been issued in these fields. Second, the politics of Islamic law in the future must build maintain the Islamic law and renewal (tajdid) of Islamic law in Indonesian context.Keywords: Political Law of National Laws